Influence of lateral muscle loading in the proximal femur after fracture stabilization with a Trochanteric Gamma Nail (TGN) - Kriskrai Sitthiseripratip (2018)
The purpose of this study was to investigate the influence of lateral muscle loading on the stress/strain distributions of the trochanteric Gamma nail (TGN) fixation within the healed, trochanteric and subtrochanteric femoral fractures by means of a finite element method. The effect of three muscle groups, the abductors (ABD), the vastus lateralis (VL) and the iliotibial band (ITB), were investigated. The analytical results showed that addition of lateral muscle forces, iliotibial band and vastus lateralis, produced compensation of forces and reduction of bending moments in the bone and in the trochanteric Gamma nail especially in the lateral aspect. The iliotibial band produced a higher impact as compared to the vastus lateralis. Therefore in the finite element analysis of the proximal femur with the trochanteric Gamma nail fracture fixation should include the lateral muscle forces to simulate load condition with maximal physiological relevance to the closed nailing technique.